Intra-household decision-making, production diversity, and dietary quality: a panel data analysis of Ethiopian rural households - Orkhan Sariyev; Tim K. Loos; Ling Yee Khor (Food Security, 2020)
Considering that rural poor are mostly subsistence farmers, it seems plausible that production diversity could lead to better nutrition for these farmers. The association between production and dietary diversity is complex, and this complexity demands rigorous empirical analyses and more attention to gendered aspects of intra-household decision-making. We employ panel data analyses of 363 Ethiopian smallholders surveyed in 2014 and 2016 to test for this phenomenon, and to explore the association of women's participation in decision-making with both production and consumption diversity. Results show that, diversification can be a strategy to improve the diets, but only of rural poor who have limited non-farm income, who are distant to the markets and mostly subsistence oriented. Moreover, female participation in decision-making associates with higher diversity both in terms of production and consumption, but it does not modify the magnitude of the association between production and dietary diversity. Our analyses contribute to the enriching literature on the linkage between production diversification and dietary diversity. We study this complex relationship in-depth and show that the gendered aspect of intra-household decision-making is an important covariate for both production diversity and dietary quality.
Keywords: 630; Decision-making; Dietary diversity; Production diversity; Panel data; Ethiopia; Smallholder farmers